Legal Considerations in Cross-Jurisdictional Sharing of Public Health Laboratory Services - Berkery, Molly R. (Association of Schools of Public Health, 2013)
The Centers for Disease Control and Prevention and the Association of Public Health Laboratories initiated the Laboratory Efficiencies Initiative in 2011 to help address issues related to public health laboratory (PHL) capacity to perform critically needed tests and services. One approach to improving capacity and efficiency is sharing PHL services with other states or jurisdictions. Cross-jurisdictional sharing implicates numerous federal and state laws, including federal and state privacy laws, laboratory certifications, packaging and shipping requirements for laboratory specimens, and state laws regarding fees and revenue. While federal laws generally do not present insurmountable barriers to sharing PHL services, state laws vary greatly, even within the same region of the country. This article summarizes some of the potentially relevant federal and state legal issues related to cross-jurisdictional sharing. It is important that states interested in cross-jurisdictional sharing consider all relevant laws, potential conflicts of law, as well as inconsistencies with agreements already in place among health departments and laboratories.